2015
DOI: 10.1002/asi.23561
|View full text |Cite
|
Sign up to set email alerts
|

URL decay at year 20: A research note

Abstract: All text is ephemeral. Some texts are more ephemeral than others. The web has proved to be among the most ephemeral and changing of information vehicles. The research note revisits Koehler's original data set after about 20 years since it was first collected. By late 2013, the number of URLs responding to a query had fallen to 1.6% of the original sample. A query of the 6 remaining URLs in February 2015 showed only 2 still responding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…5,6,7 In 2015, upon the twenty-year benchmark of the original data collection, Oguz and Koehler reported in JASIS that only 2 of the original links remained active. 8 A number of foundational studies, including Casserly and Bird, 9 Spinellis, 10 Sellitto, 11 Falagas, Karveli, and Tritsaroli, 12 and Wagner et al 13 have reported on linkrot occurring in professional literature. Sanderson, Phillips, and Van de Sompel provide a table of 17 well-known linkrot studies, comparing overall benchmarks, and supplying a succinct summary of the scope of each study.…”
Section: Smoking Gunsmentioning
confidence: 99%
“…5,6,7 In 2015, upon the twenty-year benchmark of the original data collection, Oguz and Koehler reported in JASIS that only 2 of the original links remained active. 8 A number of foundational studies, including Casserly and Bird, 9 Spinellis, 10 Sellitto, 11 Falagas, Karveli, and Tritsaroli, 12 and Wagner et al 13 have reported on linkrot occurring in professional literature. Sanderson, Phillips, and Van de Sompel provide a table of 17 well-known linkrot studies, comparing overall benchmarks, and supplying a succinct summary of the scope of each study.…”
Section: Smoking Gunsmentioning
confidence: 99%
“…For a medium that has become pre-eminent, its dynamism and transience has become increasingly worrisome. These concerns have been illustrated in various longitudinal studies of link rot [55] and investigations which found that during a period between 2009 and 2012, on average 11% of online resources shared on social media failed to resolve one year later [60]. In this context, it is increasingly claimed that the ephemerality of the Web demands intervention to preserve web content -in web archives -that reconstruct sites and the 'web experience' for posterity [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of content drift over time, Jones et al (2017) found that over 75 percent of the web content referenced by scholarly articles had changed from when they had originally been cited. Similarly, Oguz and Koehler (2016) found evidence of "URL decay" where only two URLs out of set of 360 were still active after approximately twenty years. Documents hosted on university websites might not be migrated to new websites, thus the continuity of access to older online files can be threatened (Bicknese, 2004).…”
Section: The Role Of Academic Libraries In Public Engagementmentioning
confidence: 90%